Reconstrucción hipotética de la llegada a España del Códice Trocortesiano en el contexto de la Real Orden de 1752 - Andrés Gutiérrez Usillos (Journal de la Société des Américanistes)
The cultural, political and administrative circumstances of the mid-18th century in the viceroyalty of New Spain would explain the sending to Spain of the pre-Hispanic Mayan document known as the Trocortesian Codex. Based on previous data indicating that the codex belonged to the family of the Counts of Cancelada, we hypothetized that the document initial destination was the Royal Cabinet of Natural History of the Mines and Royal House of Geography at Madrid. Both, the situation of this institution and the viceroy Revillagigedo’s family circustamces, would explain the route that the codex took until it reached the 6th Countess of Cancelada, who handed it over to Juan de Tro and José Ignacio Miró who, in turn, sold it to the National Archaeological Museum in 1872 and 1888.